Accessibility of Islamic Financial Services for People Living with Disabilities (PLWDs) - Shehu, Farida Mohammed; Idris, Adamu Adamu; Atah, Ummi Ibrahim; Abba, Safiyya Abubakar (Tujjar International Journal of Islamic Economics Development, 2024)
This paper explores the accessibility of Islamic financial services for People Living with Disabilities (PLWDs), a critically underserved group in financial inclusion discourse. Despite Islamic finance’s inherent principles of equity, compassion, and social justice, institutional practices often overlook the specific needs of PLWDs. The study addresses a key gap in both Islamic finance and disability rights literature by examining how inclusive or exclusive current financial systems are for this demographic. Employing a broad literature review methodology, the paper synthesizes recent academic research, regulatory frameworks, and real-world practices from countries such as Saudi Arabia, Pakistan, Malaysia, Jordan, Nigeria, and Ghana. Key findings reveal persistent barriers across physical infrastructure, digital interfaces, institutional attitudes, and financial literacy. However, promising models such as SAMA’s accessibility guidelines, Braille and voice-enabled banking in Pakistan and Jordan, and co-designed fintech platforms in Kenya and Mexico, demonstrate scalable best practices. The paper underscores the need for Islamic financial institutions to go beyond compliance and actively embrace universal design, inclusive product development, and collaborative policymaking with disability rights stakeholders. The study concludes with a call to action for regulators, Shariah boards, and Islamic financial service providers to institutionalize accessibility within core operations. Doing so aligns with both global disability inclusion goals and the Islamic ethical mandate to serve marginalized communities with dignity and equity.